The Hexa Helix Collaboration Model For Stunting Reduction: A Collaborative Governance Perspective On Public Health Improvement - Syalsabilla Nafa Adam Pinata; Nasywa Alifya; Afrijal Afrijal; Herizal Herizal; Soraya Agustina (JIIP: Jurnal Ilmiah Ilmu Pemerintahan, 2026)
This study aims to analyze the hexa-helix collaboration model in addressing stunting to improve public health. The research employs a qualitative method with a literature study approach, designed to provide an in-depth understanding of the stunting phenomenon by synthesizing and descriptively analyzing relevant data. By exploring various aspects such as community behavior, perceptions, motivations, and actions, this study seeks to gain a comprehensive perspective on the existing challenges and potential solutions. The findings indicate that stunting reduction efforts in Indonesia require a holistic and collaborative hexa-helix approach involving multiple sectors, including government, academia, the private sector, communities, media, and non-governmental organizations. Despite the presence of various strategic programs, significant challenges remain, particularly the unequal distribution of nutritious food and the suboptimal coordination across sectors. Cross-sectoral synergy and integrated interventions are therefore crucial to enhancing the effectiveness and sustainability of stunting prevention efforts.